Role of Amyloid Beta and Tau Protein in Alzheimer’s disease - Lodhi, Rajkumari; Sharma, Virendra Kumar (Journal of Pharmacy Practice and Community Medicine, 2026)
Alzheimer’s disease is the leading cause of dementia and represents the most prevalent neurodegenerative condition worldwide. It is characterized by progressive deterioration in short-term memory and cognitive abilities, eventually interfering with everyday activities and behavior. Although most cases occur sporadically, a smaller proportion is inherited, enabling the identification of specific genes that, along with neuropathological findings, provide valuable insight into the broader origins of the disease. A variety of environmental and metabolic influences, such as inflammation and vascular dysfunction, are also believed to contribute to the initiation and advancement of the disorder. Despite widespread neuronal shrinkage and synaptic loss across the cerebral cortex, the precise mechanisms responsible for these changes are still not fully understood. The primary pathological features associated with Alzheimer’s disease are amyloid-β plaques and neurofibrillary tau tangles. Although these protein accumulations have been intensively studied for decades, their exact contribution to disease progression remains uncertain. This review explores several proposed mechanisms involved in Alzheimer’s disease, including inflammation, mitochondrial impairment, oxidative stress, and disruptions in protein clearance pathways.
Keywords: Amyloid-β plaques; Alzheimer’s disease Etiology; Dementia; Neurodegeneration; Neurofibrillary Tau Tangles